"Men Fear Most What They Cannot See." sleep paralysis "Ghost Intruders" and faceless "Shadow-People"—The role of the right hemisphere and economizing nature of vision. (March 2021) - Jalal, Baland
Abstract: Sleep paralysis is a curious condition where the paralyzed person may hallucinate terrifying ghosts. These hypnogogic and hypnopompic visions are common worldwide. They often entail seeing and sensing shadow beings; although hallucinating full-fledged figures (e.g., cat-like creatures and witches) are not uncommon. In this paper, I propose a neuroscientific account (building on previous work) for why people see ghosts during sleep paralysis and why these tend to manifest as faceless shadows. This novel venture considers the distinct computational styles of the right and left hemisphere and their functional specializations vis-à-vis florid intruder hallucinations and out-of-body experiences (OBEs) during these dream-like states. Additionally, I provide a brain-based explanation for dissociative phenomena common during sleep paralysis. Specifically, I posit that these ghost hallucinations and OBEs are chiefly mediated by activity in key regions in the right hemisphere; and outline how the functional organization of the visual system (evoking concepts like surface interpolation) and its economizing nature (i.e., proclivity to minimize computational load and take short-cuts) can explain faceless humanoid-shadows and sensed presence hallucinations during sleep paralysis; and how the hypothalamus and anterior cingulate may be implicated during related dissociative states. Ultimately empirical research must shed light on the validity of this account. If this hypothesis is correct, patients with right hemisphere damage (i.e., in implicated areas) should be less likely to hallucinate ghosts during sleep paralysis; i.e., compared to those with intact hemispheres or damage to the left only. It may also be possible to temporarily disable right hemisphere functions during sleep paralysis using transcranial magnetic stimulation. Accordingly, this procedure should eradicate sleep paralysis ghost hallucinations.